Relationships between somatic anxiety, cognitive anxiety, self-efficacy, and emotional intelligence levels in university physical education students - Mercader-Rubio, Isabel; Gutiérrez Ángel, Nieves; Silva, Sofia; Moisão, Ana; Brito-Costa, Sónia (Frontiers in Psychology, 2023)
From the field of psychology, one of the most studied constructs is anxiety, which has been approached from currents such as psychoanalysis to behaviorist currents, all these contributions concluding in the relevance it has in affective, rational, and emotional processes. The aim of this research is to analyze the levels of anxiety and emotional intelligence, as well as the relationship between them in a sample of university students of physical education. The sample is made up of 165 students with an average age of 20.33 years (SD = 3.44), (70.9% male and 27.9% female). Both psychological constructs were measured using the CSAI-2 questionnaire to measure cognitive anxiety, somatic anxiety, and self-confidence. And the TMMS-24 to measure emotional intelligence. The results highlight the existence of significant correlations between emotional clarity and emotional regulation, and between self-confidence and somatic anxiety. However, these results were not positive for cognitive anxiety and emotional attention. This demonstrates that sporting performance is influenced by a large number of variables, among which we cannot ignore emotions, and hence the importance of incorporating the emotional component into the sporting environment.